Literature Review: Efektifitas Metode Moist Wound Healing pada Ulkus Diabetik: Effectiveness of The Moist Wound Healing Method on Diabetic Ulcus: a Literatur Review - Desi Lestari; Indah Puspitasari; Sunirah Sunirah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
One of the complications of diabetes mellitus is the presence of ulcer wounds which cause 50% to 75% of amputation. This literature review aims to determine the effectiveness of the Moist Wound Healing method in diabetic wounds. The design of this scientific paper is a literature review search using an electronic database, namely google scholar, semantic scholar, and pubmed. The keywords used in the search were: diabetes mellitus AND moist AND diabetic ulcer. Based on a literature review of 4 articles, significant results were obtained in wound healing, namely 2-3 times faster healing. it can be concluded that the moist wound healing method can affect the healing process of diabetic ulcers and has effectiveness for wound healing.